The effectiveness of Internet-based e-learning on clinician behaviour and patient outcomes: A systematic review. (May 2016) - Sinclair, Peter M.; Kable, Ashley; Levett-Jones, Tracy; Booth, Debbie
Abstract: Background: The contemporary health workforce has a professional responsibility to maintain competency in practice. However, some difficulties exist with access to ongoing professional development opportunities, particularly for staff in rural and remote areas and those not enrolled in a formal programme of study. E-learning is at the nexus of overcoming these challenges. The benefits of e-learning have been reported in terms of increased accessibility to education, improved self-efficacy, knowledge generation, cost effectiveness, learner flexibility and interactivity. What is less clear, is whether improved self-efficacy or knowledge gained through e-learning influences healthcare professional behaviour or skill development, whether these changes are sustained, and whether these changes improve patient outcomes. Objective: To identify, appraise and synthesise the best available evidence for the effectiveness of e-learning programmes on health care professional behaviour and patient outcomes. Design: A systematic review of randomised controlled trials was conducted to assess the effectiveness of e-learning programmes on clinician behaviour and patient outcomes. Electronic databases including CINAHL, Embase, ERIC, MEDLINE, Mosby's Index, Scopus and Cochrane – CENTRAL were searched in July 2014 and again in July 2015. Quality assessment and data extraction: Studies were reviewed and data extracted by two independent reviewers using the Joanna Briggs Institute standardised critical appraisal and data extraction instruments. Data synthesis: Seven trials met the inclusion criteria for the analysis. Due to substantial instructional design, subject matter, study population, and methodological variation between the identified studies, statistical pooling was not possible and a meta-analysis could not be performed. Consequently, the findings of this systematic review are presented as a narrative review. Results: The results suggest that e-learning was at least as effective as traditional learning approaches, and superior to no instruction at all in improving health care professional behaviour. There was variation in behavioural outcomes depending on the skill being taught, and the learning approach utilised. No papers were identified that reported the effectiveness of an e-learning programme on patient outcomes. Conclusion: This review found insufficient evidence regarding the effectiveness of e-learning on healthcare professional behaviour or patient outcomes, consequently further research in this area is warranted. Future randomised controlled trials should adhere to the CONSORT reporting guidelines in order to improve the quality of reporting, to allow evaluation of the effectiveness of e-learning programmes on healthcare professional behaviour and patient outcomes.